Complexidade como uma propriedade emergente: caudas grossas, correlações de longo alcance e multifractalidade em séries temporais não estacionárias - Passos, Frederico Salgueiro (2011)
An important open problem concerns the physical origin of long-range correlations, multifractality, and fat tailed distributions observed in heteroscedastic time series associated with complex systems. Financial stylized facts provides one useful example usually not explained by traditional economic models. We investigate the behavior of an agent based model, consisting of N agents which are heterogeneous and do not interact with each other and follow simple rules. We show that fat tailed distributions, long-range correlations, heteroscedasticity and multifractality arise as N becomes large. Our findings suggest that such stylized facts can in principle arise as emergent properties.